A Case of Variceal Bleeding with Cricopharyngeal Web: A Challenge to Variceal Band Ligation - Dandi Kranthi; Debabrata Banerjee; Amol S Dahale; Abhijeet Karad; Yogesh Bade (Journal of Clinical and Diagnostic Research)
Acute Variceal Bleeding (AVB) is a life-threatening complication of portal hypertension that necessitates prompt and effective intervention. Endoscopic Variceal Ligation (EVL) is the primary treatment modality; however, anatomical variations, such as oesophageal webs, can impede the procedure. The present report describes a 40-year-old female patient presenting with haematemesis and melena. Endoscopy confirmed active variceal bleeding, but the advancement of an endoscope equipped with a band ligator was obstructed by a cricopharyngeal web, rendering EVL unfeasible. Haemostasis was initially achieved using sclerotherapy with sodium tetradecyl sulfate. Subsequent endoscopic dilation of the web with a Controlled Radial Expansion (CRE) balloon facilitated successful band ligation. The present case underscores the importance of early recognition of anatomical anomalies and highlights the need for adaptable strategies in the management of AVB, particularly in emergent settings where time is critical. The clinical implications are significant, as the case highlights a previously unreported barrier to EVL in the form of a cricopharyngeal web. It emphasises the necessity for endoscopists to consider anatomical variations when standard procedures fail. The present report contributes to the literature by documenting an unusual clinical scenario that required modification of the standard therapeutic approach to achieve haemostasis in a life-threatening situation.